Anodic Methoxylation of 2-Acyloxy-3, 3, 3-trifluoropropyl Sulfides Accompanying with [1, 2]-Rearrangement of the Acyloxy Group and Anodic Cyclization of 2-(t-Butoxycarbonyl)oxy-3, 3, 3-trifluoropropyl Sulfide. Issue 13 (1st January 2017) - Isokawa, Motoaki; Sano, Masaru; Kubota, Kiyotaka; Suzuki, Katsutoshi; Inagi, Shinsuke; Fuchigami, Toshio
Abstract : Anodic methoxylation of 2-acyloxy-3, 3, 3-trifluoropropyl sulfides was carried out in methanol containing Et3 N-3HF as a supporting electrolyte and mediator using an undivided cell to provide the corresponding α-methoxylated products and unexpected β-methoxylated products owing to [1, 2]-rearrangement of the acyloxy group in the latter case. It was also found that the regioselectivity and diastereoselectivity of the anodic methoxylation were greatly affected by the concentration of methanol in an electrolytic solvent, electrolytic temperature, and bulkiness of acyloxy group. This is the first example of anodic methoxylation of sulfides accompanying with rearrangement of an acyloxy group. Furthermore, anodic intramolecular cyclization of 2-( t -butoxycarbonyl)oxy-3, 3, 3-trifluoropropyl sulfide was achieved in 0.01 M Et3 N-3HF/MeCN eliminating a t -butyl cation to provide the corresponding trifluoromethylated ethylene carbonate derivative in good yield.